2022
DOI: 10.1177/15910199221095789
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatments of intracranial vertebral and internal carotid arteries dissections: An interactive systematic review and meta-analysis

Abstract: Introduction Management of intracranial artery dissection (IAD) remains elusive in medical practice. Intracranially, vertebral artery dissection (VAD) is more commonly encountered than internal carotid artery dissection (ICAD). Deconstructive (EVT-d) and reconstructive (EVT-r) endovascular techniques have been utilized to treat VAD and ICAD. This meta-analysis investigates the safety and efficacy of EVT-r and EVT-d in the management of VAD and ICAD. Methods The literature was searched for all studies with cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The randomized CADISS clinical trial showed no significant difference between antiplatelet and anticoagulant treatments in rates of further ischaemic stroke, subarachnoid haemorrhage, and death at 3 months [ 22 ]. To date, symptomatic intracranial artery dissection, including vertebral artery dissection, is a significant challenge for clinicians due to the evidence of poor clinical outcomes and limited conservative and interventional management [ 23 ]. Since the introduction of endovascular treatments for intracranial artery dissection two decades ago, it has evolved from simple coiling or balloon occlusion for parent arterial sacrifice to more selective and delicate reconstruction styles, including overlapping stents, stent-assisted coils, and flow diverters [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The randomized CADISS clinical trial showed no significant difference between antiplatelet and anticoagulant treatments in rates of further ischaemic stroke, subarachnoid haemorrhage, and death at 3 months [ 22 ]. To date, symptomatic intracranial artery dissection, including vertebral artery dissection, is a significant challenge for clinicians due to the evidence of poor clinical outcomes and limited conservative and interventional management [ 23 ]. Since the introduction of endovascular treatments for intracranial artery dissection two decades ago, it has evolved from simple coiling or balloon occlusion for parent arterial sacrifice to more selective and delicate reconstruction styles, including overlapping stents, stent-assisted coils, and flow diverters [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, symptomatic intracranial artery dissection, including vertebral artery dissection, is a significant challenge for clinicians due to the evidence of poor clinical outcomes and limited conservative and interventional management [ 23 ]. Since the introduction of endovascular treatments for intracranial artery dissection two decades ago, it has evolved from simple coiling or balloon occlusion for parent arterial sacrifice to more selective and delicate reconstruction styles, including overlapping stents, stent-assisted coils, and flow diverters [ 23 ]. As reported in a previous meta-analysis, deconstructive treatments were commonly utilized for vertebrobasilar dissections with good angiographic outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%